PENGARUH PENGOLAHAN TANAH DAN PEMBERIAN BAHAN ORGANIK (BLOTONG DAN ABU KETEL) TERHADAP POROSITAS TANAH DAN PERTUMBUHAN TANAMAN TEBU PADA ULTISOL - Carolina Eva Nita; Bambang Siswanto; Wani Hadi Utomo (Jurnal Tanah dan Sumberdaya Lahan, 2015)
The use of agricultural mechanization in the form of tractors and earth moving will have an impact on soil porosity, soil bulk density and soil's ability to store water. The purpose of this study was to determine the effect of soil tillage and organic matter (filter cake and boiler ash) on soil porosity and high growth of sugarcane (Saccharum officinarum L.). The experiment used a randomized block design with 5 treatments and 3 replications, K0 = Control (Plowing 2 times + Harrowing 1 time + Furrowing 1 time), K1 = (Plowing 2 times + Harrowing 1 time + Furrowing 1 time filter cake  40 t ha-1 and boiler ash 40 t ha-1 spread), K2 = (Plowing 1 time + Harrowing  1 times + Furrowing 1 times filter cake  40 t ha-1 and boiler ash 40 t ha-1 spread), K3 = (Sub soiling 2 times + Harrowing 1 times + Furrowing 1 time filter cake 40 t ha-1 and boiler ash 40 t ha-1 spread), K4 = (Sub soiling 2 times + Harrowing 1 time + Furrowing 1 time filter cake  40 t ha-1 and boiler ash 40 t ha-1 included in the bolt). Tillage Sub soiling 2 times + Harrowing 1 time + Furrowing 1 time filter cake 40 t ha-1 and boiler ash 40 t ha-1 included in the bolt (K4) was able to increase the porosity of the soil that was equal to 50.2% and increased the sugar cane plant height of 3 MST, 6 and 9 MST, respectively 11.62 cm, 17.35 cm and 34.59 cm